Developing Teacher Competencies Of Prospective Teacher Students In The Faculty Of Education Based On A Statistical Mini-Research Project - Dirgantoro, Kurnia Putri Sepdikasari; Listiani, Tanti; Soesanto, Robert Harry (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The Faculty of Education is dedicated to preparing teacher candidates. Ideally, every course students take should contribute to developing their teaching competencies. Within this framework, Educational Research Statistics is one of the mandatory courses for candidates at the Faculty of Education, Pelita Harapan University. In this course, students are expected to work collaboratively on a mini-research project for 1 semester, where they are trained to identify and solve problems through statistical procedures. At the end of the project, students are then expected to present the obtained outputs to their classmates. Therefore, this study aimed to carry out the following objectives: 1) Examine the level of differences in teacher competencies among students before and after the implementation of the mini-research project, and 2) Analyze the effectiveness of the project in strengthening teacher competencies of students. A mixed-method approach was implemented in this case, with 47 students employed as the experimental sample. This study used teacher competency tests and questionnaires as instruments. The processing of the results was also analyzed quantitatively and qualitatively. This research provides results: 1) there are significant differences between teacher competencies in students before and after the implementation of mini-research projects, and 2) the implementation of mini-research projects effectively strengthens the competence of student teachers. Therefore, every course must consider the best learning strategy to strengthen student teachers' competence.